The Mandoa Funeral Tradition as Informal Islamic Education: Exploring Moral Formation and Intergenerational Religious Socialization - Salsabila Nadia Putri; Oktari Kanus (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study examines the mandoa funeral tradition in Nagari Pakandangan, West Sumatra, Indonesia, as a form of informal Islamic education that contributes to moral formation and intergenerational religious socialization. Although previous studies have predominantly interpreted funeral traditions as cultural heritage, ritual practice, or expressions of local identity, limited scholarly attention has been devoted to their educational functions in transmitting Islamic values and shaping community character. Therefore, this study aims to explore the moral values embedded within the mandoa tradition and analyze the processes through which religious values, social norms, and cultural practices are transmitted across generations. This research employed a qualitative ethnographic design conducted over four months through participant observation, in-depth interviews with 18 key informants, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing and verification. The findings reveal that mandoa serves as a holistic educational space that cultivates three interconnected dimensions of morality: devotion to Allah through collective worship, remembrance, and prayer; social morality through mutual assistance (ta‘awun), empathy, solidarity, and communal responsibility; and environmental morality through collective care for cleanliness and public comfort. Furthermore, religious socialization occurs through active participation, role modeling by religious and community leaders, structured community involvement, and the repeated habituation of younger generations in religious and social activities. The originality of this study lies in conceptualizing mandoa as an integrated mechanism of informal Islamic education, moral formation, intergenerational religious socialization, and cultural transmission. This study contributes to the fields of Islamic education, sociology of religion, and cultural studies by demonstrating how local religious traditions function as community-based educational institutions that preserve Islamic values, strengthen social cohesion, and sustain cultural continuity amid contemporary social change.